Feasibility of a new endoscopic suturing device: a first Western experience (with video) - Scheppach, Markus W.; Nagl, Sandra; Muzalyova, Anna; Classen, Johanna; Messmann, Helmut; Ebigbo, Alanna (Gastrointestinal endoscopy, 2025)
Endoscopic hand suturing (EHS) is a new technique for the closure of mucosal defects in the GI tract. Although this method was tested for wound closure after endoscopic submucosal dissection (ESD) in Japan, a feasibility test in a Western setting is lacking. In this study, we present our first experience with EHS for different indications and in different anatomic locations. The technical success of EHS and suturing speed were retrospectively determined for all available EHS cases in our center. Technical success was defined as complete closure of the mucosal defect or visually tight fixation of the target. A total of 19 EHS procedures were performed in 17 patients (mean age, 54.9 years; standard error of the mean [SEM], 4.2 years; male, 53% [n = 9]). Technical success was achieved in 78.9% (n = 15). Total EHS operation time was 40.0 minutes (SEM, 3.1 minutes) with 3.3 minutes (SEM, 0.2 minutes) per single stitch. In a constant team of endoscopist and assistant, mean stitch times declined significantly from the first 4 to the second 4 of 8 cases (4.0 [SEM, 0.6] vs 2.3 [SEM, 0.2] minutes, P = .02). EHS was technically feasible and applicable in different anatomic locations. Further studies may elucidate a possible effect on adverse event rates of endoscopic resections.